Body Composition, Eating Habits, and Disordered Eating Behaviors among Adolescent Classical Ballet Dancers and Controls - Panagiota Chaikali; Ioanna Kontele; Maria G. Grammatikopoulou; Eleftheria Oikonomou; Theodoros N. Sergentanis; Tonia Vassilakou (MDPI AG, 2023)
Adolescent classical ballet dancers are nutritionally vulnerable, as they try to retain a lean body shape during a life period of high nutritional requirements due to rapid growth. Studies conducted on adult dancers have indicated a high risk for the development of disordered eating behaviors (DEBs), but research on adolescent dancers remains scarce. The aim of the present case-control study was to compare the body composition, dietary habits, and DEBs of female adolescent classical ballet dancers and their non-dancer same-sex peers. Self-reported questionnaires, namely the Eating Attitudes Test-26 (EAT-26) and a 19-item Food Frequency Questionnaire (FFQ), were used for the assessment of habitual diet and DEBs. The assessment of body composition included the measurements of body weight, height, body circumference, and skinfolds and bioelectrical impedance analysis (BIA). The results indicate that the dancers were leaner than the controls, with lower weight, BMIs, and hip and arm circumferences, leaner skinfolds, and less fat mass. No differences were observed between the two groups regarding eating habits and the EAT-26 scores, but almost 1 out of 4 (23.3%) participants scored ≥ 20, indicative of DEBs. Participants with an EAT-26 score ≥ 20 had significantly higher body weight, BMIs, body circumferences, fat mass, and fat-free mass than those with a score < 20. Adolescents must be educated on nutrition and healthy methods to control body weight through evidence-based information and programs, and whenever appropriate, also through individual counseling by the appropriate health professionals.